The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.electacta.2016.09.103
|View full text |Cite
|
Sign up to set email alerts
|

Effect of crystalline structure on the electrochemical properties of K0.25V2O5 nanobelt for fast Li insertion

Abstract: Lithium vanadium oxides and vanadates have wide attention as cathode materials for Li ion battery applications, but there has been limited study on other cation substituted vanadium compounds, which could have favorable electrochemical properties. Here we report the synthesis and electrochemical properties of aggregated K0.25V2O5 nanobelts and the optimization of the crystalline structure for fast Li ion insertion. We propose a partial melting and self-alignment mechanism to produce the aggregated nanobelts. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 68 publications
3
6
0
Order By: Relevance
“…The phenomenon related to gradual increasing capacity may be attributed to high electrode polarization, considering more disorder in the crystal and increasing flexible lithium diffusion paths with the cycles going . Similar phenomena have also been found in K 0.25 V 2 O 5 , Na 1.08 V 3 O 8 , β‐Na 0.33 V 2 O 5 , and CaV 6 O 16 ⋅ 3 H 2 O . Additionally, the coulombic efficiency keeps fading, which can be caused by poor electrical conductivity or loss of some material contacting with the current collector (the structure morphology changes during Li insertion/extraction) …”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…The phenomenon related to gradual increasing capacity may be attributed to high electrode polarization, considering more disorder in the crystal and increasing flexible lithium diffusion paths with the cycles going . Similar phenomena have also been found in K 0.25 V 2 O 5 , Na 1.08 V 3 O 8 , β‐Na 0.33 V 2 O 5 , and CaV 6 O 16 ⋅ 3 H 2 O . Additionally, the coulombic efficiency keeps fading, which can be caused by poor electrical conductivity or loss of some material contacting with the current collector (the structure morphology changes during Li insertion/extraction) …”
Section: Resultssupporting
confidence: 68%
“…In the first cycle, four cathodic peaks are located at potentials of 3.19, 2.81, 2.55, and 1.65 V, indicating a complicated lithium ion intercalation process, and three anodic peaks located at 2.45, 2.82, and 3.28 V, due to the lithium ion extraction from the host electrode material. Similar multi‐step complex lithium ion (de)intercalation behaviors have also been found in other vanadium based compounds, such as NaV 3 O 8 , Na 0.76 V 6 O 15 , K 0.25 V 2 O 5 , etc. The splitting of many redox peaks was ascribed to the different lithium sites with energy differences for holding the lithium ions .…”
Section: Resultssupporting
confidence: 66%
“…[10c] The gradual capacity increase in the second stage may have relation to high electrode polarization and Li + diffusion paths become more flexible with increased cycling numbers. [27] Similar phenomena have also been found in other vanadium bronze such as K 0.25 V 2 O 5 , [28] Mg 0.25 V 2 O 5 • H 2 O, [10b] Ca 0.24 V 2 O 5 [29] and NH 4 V 4 O 10. [11] In the meantime, it is observed that the Coulombic efficiency gradually increases along with the increment of current rate.…”
Section: Resultssupporting
confidence: 75%
“…The full spectrum of the XPS indicates the presence of the V, O, and K elements (Figure S3). K2p 1/2 and K2p 3/2 peaks were observed at 295.2 and 292.4 eV, respectively, confirming the successful intercalation of K + into V 2 O 5 , and the formation of K−O chemical bonds (Figure a) . At the same time, V2p 3/2 , V2p 1/2 , and O1s peaks were observed at 517.2 eV, 524.5 eV, and 530.1 eV, respectively (Figure b), demonstrating the existence of V−O chemical bonds …”
Section: Resultsmentioning
confidence: 99%
“…The detailed crystallographic information of K 0.5 V 2 O 5 is shown in Figure S4. By comparing the simulated XRD diffraction patterns of V 2 O 5 and K 0.5 V 2 O 5 , a strong peak at around 7.8° was observed in that of K 0.5 V 2 O 5 , which corresponds to the (100) crystal plane …”
Section: Resultsmentioning
confidence: 99%